Paternalism and the Justification of Education - Giesinger, Johannes (Philosophical Inquiry in Education, 2019)
The problem of paternalism, widely discussed in moral and political philosophy, has not received much attention in the philosophy of education. Yet Johannes Drerup claims that paternalism should be considered ‘an indigenous concept’ of educational theory, and ‘the indigenous model of justification’ in education. This essay explores Drerup’s claim, considering conceptual and normative aspects of paternalism and education. The first idea put forward in this essay is that, in the search for ‘indigenous’ educational concepts, we should focus on education, not paternalism. In a second step, however, this essay makes clear that the debate on paternalism might inspire conceptual and normative discussions in the philosophy of education. In this vein, a core notion of educational practice (as educational address in asymmetric constellations) is sketched, and it is outlined what it means to justify education. The idea is that certain forms of educational address require a specific form of (quasi-paternalistic) justification that goes beyond the justification of educational aims.